Implementasi Metode Simple Multi Attribute Rating Technique pada Sistem Pendukung Keputusan Pemilihan Guru Berprestasi - Hay's, Riyan Naufal; Muttaqin, Zaenal; Suhendar, Akip; Elisa, Dina (Jurnal Informatika Universitas Pamulang, 2021)
Selection of Outstanding Teachers is an activity that is routinely carried out by the District Level at the end of each academic year. The manual system often causes difficulties for supervisors when the final assessment process is fast and precise and the selection is subjective, this happens because all criteria have not been given weight. With a good system, it can help facilitate the selection process for outstanding teachers. Therefore, a Decision Support System (SPK) is needed using the SMART (Simple Multi Attribute Rating Technique) method, which means multi-attribute optimization and accurate solutions to facilitate supervisors in processing teacher selection. achievers. This research was proposed to build a DSS capable of providing objective decision recommendations and able to increase the speed of the decision-making process. This research has succeeded in applying the SMART method for the selection of outstanding teachers at the Lebak Wangi sub-district, Serang district.